Comparison of Limited-Undermining Lipoabdominoplasty and Traditional Abdominoplasty Using Laser Fluorescence Imaging. (July 2014) - Roostaeian, Jason; Harris, Ryan; Farkas, Jordan P.; Barton, Fritz E.; Kenkel, Jeffrey M.
Background: Body contouring that involves abdominoplasty and/or liposuction is a common cosmetic surgery procedure. Although single-staged lipoabdominoplasty has gained popularity, safety concerns remain. Objectives: The authors compared abdominal flap perfusion and overall complication rates for traditional abdominoplasty and limited-undermining lipoabdominoplasty. Methods: Eighteen abdominoplasty patients were evaluated in a prospective study. All patients were nonsmokers and lacked major comorbidities. The control group (n = 9) underwent traditional abdominoplasty with wide undermining. The study group (n = 9) underwent abdominoplasty with limited undermining as well as liposuction of the abdominal flap. The groups were similar with respect to age and body mass index. Patients received follow-up for an average of 97 days. Fluorescence imaging was utilized for perfusion studies. Results and complications were documented, and statistical significance was ascertained via the Student t test. Results: Neither group had major complications or revisions. Minor complications included an exposed suture, resulting in delayed wound healing, in the control group. A patient in the study group had a small area of fat necrosis and a small seroma, neither of which required further treatment. No significant difference in abdominal flap perfusion was found between the control (57%) and study (50%) groups based on fluorescence levels relative to a designated baseline reference marker. Conclusions: Results of the study indicate that no significant differences exist between the 2 operations with respect to the rates of abdominal flap perfusion or complications. Level of Evidence: 3